PENANGANAN TINDAK PIDANA PENCABULAN TERHADAP DAN OLEH ANAK UMUR DIBAWAH 12 TAHUN - Fadly, Ovan Setyawan; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
In cases of violence against children, it can take the form of rape, obscene acts, sexual disclosure and other forms of sexual crimes. In this case, there was a case in Tangerang Regency where there was an act of sexual abuse against a minor, the victim named DAA aged 7 years, carried out by a child perpetrator named AP aged 11 years. The problem is how to handle criminal cases against children under 12 years old. This type of research is normative juridical research which is supported by empirical juridical research with qualitative research consisting of primary data and secondary data, both of which support each other. The legal effort to resolve criminal offenses under the age of 12 is by carrying out diversion. From the results of the diversion agreement: peace can take the form of: with or compensation for losses, handing it back to parents/guardians, participation in education/training at educational institutions or LPKS, community service.Keywords: child molestation, child perpetrators, diversion